CLINICAL AND IMMUNOLOGICAL FEATURES OF ALLERGIC DISEASES IN ADOLESCENCE AND YOUTH (American Journal of Interdisciplinary Research and Development, 2024)
This article highlights current issues in the study of clinical and anamnestic features of the course of allergic diseases in adolescence and young adulthood.